Lung Cancer Induces NK Cell Contractility and Cytotoxicity Through Transcription Factor Nuclear Localization - Wong, Darren Chen Pei; Lee, E Hui Clarissa; Er, Junzhi; Yow, Ivan; Koean, Ricky Abdi Gunawan; Ang, Owen; Xiao, Jingwei; Low, Boon Chuan; Ding, Jeak Ling (Frontiers in Cell and Developmental Biology, 2022)
Actomyosin-mediated cellular contractility is highly conserved for mechanotransduction and signalling. While this phenomenon has been observed in adherent cell models, whether/how contractile forces regulate the function of suspension cells like natural killer (NK) cells during cancer surveillance, is unknown. Here, we demonstrated in coculture settings that the evolutionarily conserved NK cell transcription factor, Eomes, undergoes nuclear shuttling during lung cancer cell surveillance. Biophysical and biochemical analyses revealed mechanistic enhancement of NK cell actomyosin-mediated contractility, which is associated with nuclear flattening, thus enabling nuclear entry of Eomes associated with enhanced NK cytotoxicity. We found that NK cells responded to the presumed immunosuppressive TGFβ in the NK-lung cancer coculture medium to sustain its intracellular contractility through myosin light chain phosphorylation, thereby promoting Eomes nuclear localization. Therefore, our results demonstrate that lung cancer cells provoke NK cell contractility as an early phase activation mechanism and that Eomes is a plausible mechano-responsive protein for increased NK cytotoxicity. There is scope for strategic application of actomyosin-mediated contractility modulating drugs ex vivo, to reinvigorate NK cells prior to adoptive cancer immunotherapy in vivo.